Pesantren’s Practical Logic: A Bourdieusian Analysis of Pragmatic Choices and Symbolic Resistance Towards Islamic Banks - Yaqin, Ainul; Sari, Refani Andina; Suparjo (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2026)
This study investigates the paradox of traditional, NU-affiliated pesantren (Islamic boarding schools) that continue to use conventional banking services amidst the massive expansion of Islamic banking. Using Pierre Bourdieu’s sociological framework of practice, this article aims to deconstruct the social logic behind this choice, which is often dismissed as inconsistent. Through a qualitative case study method, this research finds that this choice is not an anomaly but a coherent "practical logic" (nalar praktis). This logic manifests in two simultaneous forms. First, a pragmatism driven by a habitus that prioritizes efficiency, community accommodation, and ease of access. This choice is also a rational adaptation to a banking arena dominated by conventional infrastructure. Second, a symbolic resistance emerging from a critical habitus that is skeptical of Islamic banks, often viewing them as "merely different in terminology". This resistance also serves as a strategy to protect symbolic capital (marwah, or dignity), which is legitimized by the flexibility of NU’s fiqh (Islamic jurisprudence), which permits such transactions for the sake of public good (maslahah). In conclusion, this choice is a rational-social strategy, not an inconsistency. The implication is that Islamic banks must shift from label-based marketing to a relational approach built on trust.